Multilevel inverter application for railway traction motor control - Vo Thanh Ha; Pham Thi Giang; Phuong Vu (Bulletin of Electrical Engineering and Informatics, 2022)
This paper will present why choosing a 7-level reverse voltage source fed to three-phase induction motors to the railway traction motor. In addition, this paper shows the implementation of space vector pulse width modulation (SVPWM) and the math model of induction motor, stator currents, and speed controller design of electric traction drive system based on field-oriented control (FOC). By MATLAB/Simulink method, this multi-level inverter in FOC structure reduces total harmonic distortion (THD) more than other multi-level inverters such as 3 and 5-level inverter. Furthermore, this FOC control structure combined with 7-level inverter improved speed and torque responses required for railway traction motor load.